Localização e mapeamento em terrenos irregulares utilizando robôs móveis - Douglas Guimaraes Macharet (2009)
It is remarkable the increase in the use of robots in several areas and applications, especially mobile robots, those with capacity to move through the environment. Thus, it is also growing the demand to provide autonomy to the robots, reducing or eliminating the need for human supervision. A basic thing for a mobile robot to be capable of perform its tasks is to have the knowledge of its location. When you move into an indoor environment the condition of the floor is of little relevance, as it may be considered plan, however, when you go outdoor, a number of problems are related to the terrain, such as holes, slopes, amongothers, and that should be considered for a safe navigation. Considering that, this work proposes the development of a localization and mapping system for mobile robots navigating in outdoors environments with uneven terrain.